Tarificación de bonos sobre catástrofes (cat bonds) con desencadenantes de índices de pérdidas. Modelación mediante un proceso de Ornstein-Uhlenbeck - María José Pérez-Fructuoso (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
– This paper develops a continuous-time random model of loss index triggers for cat bonds on the basis of the loss amount incurred until their maturity. Assuming that total loss amount due to a catastrophe is defined as the sum of the incurred loss amount plus the incurred-but-not-yet reported loss amount, we model the decreasing linear dynamics of the latter amount by means of an additive Brownian process (or Ornstein Uhlenbeck process); and get the former by the difference between the total loss amount and the incurred-but-not-yet-reported loss amount. Finally, we test the validity of the model by estimating its core parameters and by contrasting the goodness of fit through a data series of six floods occurred in several Spanish cities prone to suffer such kind of catastrophes.
Keywords: C51; C52; 330; catastrophe bonds; incurred-but-not-yet-reported loss amount; incurred loss amount; claim reporting rate; loss index trigger; Ornstein- Uhlenbeck process